Mapeamento de regiões genômicas associadas com resistência ao míldio e à helmintosporiose em sorgo - Ana Luiza Soares Pereira de Paula (2023)
Sorghum is the fifth most cultivated cereal worldwide. It is highly adaptable to abiotic stresses and has a wide range of uses, including human, animal and industrial food. Among the limiting factors for sorghum production are leaf diseases, such as downy mildew caused by the oomycete Peronosclerospora sorghi and leaf blight, caused by the fungus Exserohilium turcicum, which are responsible for significant yield losses in the field. Foliar diseases can be controlled by chemical methods and proper management of the sorghum crop. However, the development of resistant cultivars is a sustainable alternative to control downy mildew and leaf blight, aiming to reduce production costs and environmental contamination, and to increase yield. The objective of this study was to identify genomic regions associated with resistance to downy mildew and leaf blight in a population of sorghum recombinant inbred lines derived from a cross between lines QL3 (resistant parent) and ATF14B (susceptible parent). The main results were the identification of three genomic regions associated with resistance to downy mildew and six with resistance to leaf blight, which can be targets to search for resistance genes and for sorghum breeding programs.